Enhancement of red color development in 'Mahajanaka' mango fruit exocarp with sugar application - Lueangprasert K. (2014)
Red color in 'Mahajanaka' mango fruit is a very important attribute for market acceptance. This study is therefore aimed at enhancing red color development of 'Mahajanaka' mango fruit exocarp with sugar application. Fruits at 77 days after full bloom (DAFB) were treated with either 5 and 10% fructose or 5 and 10% sucrose. The treatment was repeated at 84 and 91 DAFB. Non-treated fruit served as control. Fruit were harvested at 7-day interval starting at 98 DAFB until full maturity at 119 DAFB. The red color represented by a * value was greater in sugar-treated fruit than that of the control. Anthocyanin content gave the same result as red color development in each treatment. The reducing sugar content and phenylalanine ammonia lyase activity were determined and their role in red color development was discussed. Fructose and sucrose were found to promote red color development in 'Mahajanaka' mango fruit exocarp.